MODERN APPROACHES ON DEFINING FOOD QUALITY ON THE EU MARKET - Chirimbu, Sebastian; Burda, Alexandru (Annals of Spiru Haret University. Economic Series, 2013)
This paper seeks to prove that, on the EU food market, foodstuff quality presently has a very active complex dynamic dimension determined by the current consumer – agricultural and food industry relationship, apart from its technical dimension as derived from quality standards. This relationship comes as the result of the deep transformation that the food market has undergone in EU member states following the target-oriented action of the European Union aimed at solving the historical food-related issue of its members. Understanding the phenomena characteristic of the current food demand-supply relationship on the EU agricultural and food market and the way this market functions is very important for Romania’s integration in the European Union. This relevance derives both from economic aspects that these phenomena imply and social implications for everyday life.